The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/hipo.22296
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of stress‐induced hippocampal volume changes in mice that are susceptible or resilient to chronic social defeat

Abstract: Hippocampal shrinkage is a commonly found neuroanatomical change in stress-related mood disorders such as depression and post-traumatic stress disorders (PTSD). Since the onset and severity of these disorders have been found to be closely related to stressful life events, and as stress alone has been shown to reduce hippocampal volume in animal studies, vulnerability to mood disorders may be related to a susceptibility to stress-induced hippocampal shrinkage. However, a smaller hippocampal volume before stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…In addition, levels of NA are elevated in depressed patients [25]. An important result in this work is that CRS induce significant increase of hippocampal NA concentration (p<0.01), which confirm that the hippocampus is particularly sensitive to chronic stress [26], [27]. In a study by Leonard [25], significant negative correlations between aggressive responses and the DA synthesis capacity were observed especially in the midbrain.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, levels of NA are elevated in depressed patients [25]. An important result in this work is that CRS induce significant increase of hippocampal NA concentration (p<0.01), which confirm that the hippocampus is particularly sensitive to chronic stress [26], [27]. In a study by Leonard [25], significant negative correlations between aggressive responses and the DA synthesis capacity were observed especially in the midbrain.…”
Section: Discussionsupporting
confidence: 71%
“…The prefrontal cortex connects with regions of the brain that govern emotional behavior and stress responses, such as the amygdala, hypothalamus, and midbrain periaqueductal gray [1]. In addition, the hippocampus is a region that plays a crucial role in learning and memory and is an area also particularly susceptible to chronic stress [2], [3]. The monoaminergic-sympathetic nervous systems play important roles in maintaining homeostasis by inducing various physiological and behavioral changes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic immobilization stress in rat was without effect on hippocampal volume (Henckens et al, 2015). In mice that were susceptible to CSD in terms of decreased social avoidance, there was no increase in hippocampal volume post-versus pre-CSD, whereas there was an increase in hippocampal volume in control and resilient CSD mice (Tse et al, 2014). An ex vivo MRI study reported that hippocampal volume correlated positively with social avoidance score in CSD mice (Anacker et al, 2016).…”
Section: Metabolic and Structural Changes In Cps Micementioning
confidence: 94%
“…Decreases in hippocampus and amygdala volumes have also been described in post-traumatic stress (PTSD) (Chao et al, 2013; Chao et al, 2014; Gilbertson et al, 2002; Starcevic et al, 2014), and white matter microstructural predispositions in PTSD indicate that such structural differences reflect long-term vulnerability (Sekiguchi et al, 2014), as also observed for chronic back pain (Mansour et al, 2013). In humans, amygdala response properties seem to indicate risk for developing PTSD (McLaughlin et al, 2014), and in rodents, susceptibility to stress response is dependent on hippocampal volume and functional processing (Nalloor et al, 2014; Tse et al, 2014). Chronic tinnitus, a persistent unpleasant sensation of ringing or buzzing in the ear, is also now characterized as a dysregulation of the limbic network, mainly due to hyperactivity of the ventral striatum coupled with decreased grey matter in the medial prefrontal cortex (Leaver et al, 2011).…”
Section: Mechanistic Parallels Between Stress Anxiety Depression Anmentioning
confidence: 99%